Liver macrophage-derived exosomal miRNA-342-3p promotes liver fibrosis by inhibiting HPCAL1 in stellate cells - Wenshuai Li; Lirong Chen; Qi Zhou; Tiansheng Huang; Wanwei Zheng; Feifei Luo; Zhong Guang Luo; Jun Zhang; Jie Liu (Human Genomics)
Abstract Background The progression of liver fibrosis involves complex interactions between hepatic stellate cells (HSCs) and multiple immune cells in the liver, including macrophages. However, the mechanism of exosomes in the crosstalk between liver macrophages and HSCs remains unclear. Method Exosomes were extracted from primary mouse macrophages and cultured with HSCs, and the differential expression of microRNAs was evaluated using high-throughput sequencing technology. The functions of miR-342-3p in exosomes were verified by qPCR and luciferase reporter gene experiments with HSCs. The function of the target gene Hippocalcin-like protein 1 (HPCAL1) in HSCs was verified by Western blotting, qPCR, cellular immunofluorescence and co-IP in vivo and in vitro. Results We demonstrated that exosomal microRNA-342-3p derived from primary liver macrophages could activate HSCs by inhibiting the expression of HPCAL1 in HSCs. HPCAL1, which is a fibrogenesis suppressor, could inhibit TGF-β signaling in HSCs by regulating the ubiquitination of Smad2 through direct interactions with its EF-hand 4 domain. Conclusion This study reveals a previously unidentified profibrotic mechanism of crosstalk between macrophages and HSCs in the liver and suggests an attractive novel therapeutic strategy for treating fibroproliferative liver diseases. Graphical Abstract